The Role of Conglomerates in Chile - Zingales, Luigi (Estudios de Economía, 2025)
In this article, I assess conglomerates in Chile have affected product market competition. The analysis starts with a review of the efficiency and rent-seeking for the existence of conglomerates. The prima facie evidence fails to find efficiency reasons for the existence of conglomerates in Chile, while it is compatible with rent-seeking explanations. For this reason, I analyze various rent-seeking explanations in detail. The evidence suggests that conglomerates in Chile enjoy and advantage in gaining political influence and market power and that this political influence and market power have the potential of distorting product market competition. I present a series of proposals to limit the rent-seeking dimensions of conglomerates.